Legal Analysis of Digital Trade in Indonesia Based on Law Number 11 of 2008 concerning Electronic Information and Transactions - Nurtresna, Robby (Fox Justi : Jurnal Ilmu Hukum, 2025)
The transformation of conventional trade into digital trade in Indonesia continues to increase along with the development of information technology. Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE) is the main legal basis that regulates this activity. This study aims to evaluate the effectiveness of the ITE Law in regulating digital trade, especially regarding consumer and business actor protection. By using the normative legal method, a legal research approach that examines the main legal materials, such as laws and regulations, legal theory, and legal concepts. This approach is also known as the literature approach, the data used uses secondary data consisting of primary, secondary, and tertiary legal materials. The data obtained were collected using literature study techniques and analyzed using analytical descriptive techniques. The results of the study show that the ITE Law still has deficiencies in protecting personal data, supervising online business actors, and public awareness of consumer rights. This study recommends regulatory updates, public education, and strengthening digital infrastructure to create a safer and more sustainable digital trade ecosystem